Does emotional valence modulate word recognition? A behavioral study manipulating frequency and arousal - Paulino, Catarina (2022)
Effects of emotional valence have been observed in lexical decision tasks, suggesting that valence information modulates early word recognition. However, is still unclear the processing advantage of the different valence categories, and how these advantages might be modulated by word frequency and arousal. To clarify this question, a lexical decision task was designed using emotional words as stimuli. Emotional words were divided into three categories: 60 positive, 60 negative, and 60 neutral words. Word frequency was manipulated into low and high conditions and arousal was controlled among experimental conditions (word valence and frequency). In the first experiment, 54 participants performed the task with a maximum stimuli exposure time of 2000 ms. In a follow-up experiment, 42 participants performed the same task with two shorter fixed time exposures (150 ms and 300 ms). The results were similar between experiments: positive words were recognized faster and negative words were recognized slower than neutral ones. Furthermore, this valence effect was modulated by word frequency, affecting only words that take longer to be recognized (low-frequency words). However, the valence by frequency interaction was attenuated for high-arousal words when the pressure to respond was high (short exposure time - 150 ms). Overall, the results confirm that the emotional status of a word can affect word processing at early stages when automatic processes are taking place.